Doing gender locally: The importance of 'place' in understanding marginalised masculinities and young men's transitions to 'safe' and successful futures. Issue 4 (November 2017) - Ward, Michael R. M.; Tarrant, Anna; Terry, Gareth; Featherstone, Brid; Robb, Martin; Ruxton, Sandy
Observable anxieties have been developing about the position of boys and young men in contemporary society in recent years. This is expressed as a crisis of masculinity, in which place is often implicitly implicated, but is rarely considered for its role in the shaping of young men's practices, trajectories and aspirations. Drawing on research conducted with young people who accessed a range of social care support services, this article argues that transition means different things for young men in different locales and that local definitions of masculinity are required to better understand young men's lives and the opportunities available to them. The authors argue that home life, street life, individual neighbourhoods, regions and nations all shaped the young men's identities and the practices they (and the staff working with them) drew on in order to create successful futures and 'safe' forms of masculinity. It is suggested that this place-based approach has the potential to re-shape the 'crisis' discourse surrounding masculinity and the anxieties associated with young men.